A series of recommended tests when validating probabilistic DNA profile interpretation software. (January 2015) - Bright, Jo-Anne; Evett, Ian W.; Taylor, Duncan; Curran, James M.; Buckleton, John
Highlights: We demonstrate examples where the likelihood ratio may be easily obtained to help with the internal validation of probabilistic software. We do this by way of example using three software packages: STRmix™, LRmix, and Lab Retriever. We provide profiles and equations so the calculations may be replicated or applied to different software. Abstract: There has been a recent push from many jurisdictions for the standardisation of forensic DNA interpretation methods. Current research is moving from threshold-based interpretation strategies towards continuous interpretation strategies. However laboratory uptake of software employing probabilistic models is slow. Some of this reluctance could be due to the perceived intimidating calculations to replicate the software answers and the lack of formal internal validation requirements for interpretation software. In this paper we describe a set of experiments which may be used to internally validate in part probabilistic interpretation software. These experiments included both single source and mixed profiles calculated with and without dropout and drop-in and studies to determine the reproducibility of the software with replicate analyses. We do this by way of example using three software packages: STRmix™, LRmix, and Lab Retriever. We outline and demonstrate the profile examples where the expected answer may be calculated and provide all calculations.